Can diet change the natural history of gastrointestinal diseases? - Eamonn M M Quigley (JGH Open)
Abstract Belatedly, gastroenterologists have begun to pay attention to the role of diet in the exacerbation of gastrointestinal symptoms in many digestive disorders—a recognition that has spurred both high‐quality clinical trials and translational research into this area. It has become clear that multiple mechanisms acting either in isolation or together can induce gut symptoms and that appropriate interventions can lead to significant relief. What this review will explore is not the role of diet in the production of certain symptoms or symptom clusters, but rather whether a dietary intervention can beneficially alter the natural history of a gastrointestinal disease—a much more demanding expectation. Yet there are examples of where a diet, if sustained, can have a long‐term impact on at least some of those affected by conditions such as eosinophilic esophagitis, celiac disease, food allergy, and constipation.